2013
DOI: 10.1038/leu.2013.94
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the MYC-miRNA-EZH2 loop to suppress aggressive B-cell lymphoma survival and clonogenicity

Abstract: c-MYC (hereafter MYC) overexpression has been recognized in aggressive B-cell lymphomas and linked to adverse prognosis. MYC activation results in widespread repression of miRNA expression and associated lymphoma aggressive progression. Our recent study identified a MYC-miRNAs-EZH2 feed-forward loop linking over-expression of MYC, EZH2, and miRNA repression. Here, using a novel small-molecule BET bromodomain inhibitor, JQ1 and the EZH2 inhibitor, DZNep, we demonstrated that combined treatment of JQ1 and DZNep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
93
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 37 publications
4
93
0
Order By: Relevance
“…13,16 Intriguingly, the gene profile transcriptionally regulated by MYC varies in different cell types with relatively little overlap. 17 Two recent studies shed light on this puzzling observation, showing that, instead of activating a particular gene signature, MYC acts as an amplifier of the transcribed genes in a given cell by uploading to the promoters of active genes and enhancing their transcription.…”
Section: Myc As a Transcription Factormentioning
confidence: 99%
See 1 more Smart Citation
“…13,16 Intriguingly, the gene profile transcriptionally regulated by MYC varies in different cell types with relatively little overlap. 17 Two recent studies shed light on this puzzling observation, showing that, instead of activating a particular gene signature, MYC acts as an amplifier of the transcribed genes in a given cell by uploading to the promoters of active genes and enhancing their transcription.…”
Section: Myc As a Transcription Factormentioning
confidence: 99%
“…13,16 Intriguingly, the gene profile transcriptionally regulated by MYC varies in different cell types with relatively little overlap.…”
mentioning
confidence: 99%
“…In acute myelogenous leukemia, BRD4 is essential for tumor maintenance, and JQ1 recapitulates the effects of RNA interference of BRD4 (4,5). JQ1 was subsequently shown to have an antiproliferative effect in other hematological malignancies and solid organ tumors including glioblastoma, prostate cancer, and neuroblastoma (6)(7)(8)(9)(10). The current model of how BET inhibitors (BETi) inhibit tumor cell proliferation places inhibition of MYC as mediating activity in lymphoid tumors, with Myc-independent activity in some solid tumor types such as lung adenocarcinoma (11).…”
mentioning
confidence: 99%
“…For instance, Myc, the c-Myc oncogenic TF, is known to directly upregulate a pro-tumorigenic group of miRNAs known as the miR-17-92 cluster, however, the predominant consequence of Myc activation is widespread repression of miRNA expression (38). The involved miRNAs, including miR-26a, miR-150 and miR-195/miR-497, whose tumor-suppressing properties are to be confirmed (39)(40)(41) (42) reported that the loop consisting of c-Myc, miR-17-5p and miR-20a cluster and E2F1 modulates cellular proliferation in P493-6 cells. c-Myc simultaneously activates E2F1 transcription and limits its translation by upregulating miR-17-5p and miR-20a, allowing a tightly controlled proliferative signal.…”
Section: Reported Tf-mirna-target Gene Ffls In Cancermentioning
confidence: 99%